Factors associated with rosacea in students of a peruvian university, 2018 - Celis-Martel, Agustina (2019)
Background. Rosacea is an inflammatory and chronic dermatological condition in the central part of the face. Many factors have been proposed and studied without reaching fully accepted conclusions. Objective: To determine the association between the time of residence in the place of origin, the preferences of consumption in the diet and the degree of anxiety with rosacea in the students who attend to the dining hall of the UNHEVAL. Materials and Methods: Rosacea was diagnosed by the Rosascreen instrument and the positive cases confirmed the diagnosis with the dermatologist. To determine the association, it was used the chi-square test and the U of Mann-Whitney. Results: It was identified 168 cases and 168 controls. The average age of the participants was 21.56 + 2.73 and 61.90% women; the students come mostly from Huánuco city with a residence time of 16.29 + 3.31. It was observed in the bivariate analysis association between rosacea and gender with p = 0.03 and one OR of 0.60 (95% CI 0.39 - 0.94), association with anxiety score with a p = 0.00, association with years of current residence with p = 0.00 and association with the use of cosmetics with a p = 0.02 and one OR of 2.02 (95% CI 1.28-3.19). Conclusions: The degree of anxiety and residence time were significantly associated with rosacea.The gender was associated with a relatively lower risk of developing rosacea, while the use of cosmetics is associated with a high risk of developing.